2012
DOI: 10.1007/s00464-012-2331-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach to acute abdomen from the Consensus Development Conference of the Società Italiana di Chirurgia Endoscopica e nuove tecnologie (SICE), Associazione Chirurghi Ospedalieri Italiani (ACOI), Società Italiana di Chirurgia (SIC), Società Italiana di Chirurgia d’Urgenza e del Trauma (SICUT), Società Italiana di Chirurgia nell’Ospedalità Privata (SICOP), and the European Association for Endoscopic Surgery (EAES)

Abstract: Background In January 2010, the SICE (Italian Society of Endoscopic Surgery), under the auspices of the EAES, decided to revisit the clinical recommendations for the role of laparoscopy in abdominal emergencies in adults, with the primary intent being to update the 2006 EAES indications and supplement the existing guidelines on specific diseases. Methods Other Italian surgical societies were invited into the Consensus to form a panel of 12 expert surgeons. In order to get a multidisciplinary panel, other stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(115 citation statements)
references
References 376 publications
(338 reference statements)
0
114
0
1
Order By: Relevance
“…In 2012, grade A recommendation was made in EAES consensus statement [8] suggesting the use of diagnostic laparoscopy in suspected appendicitis and to proceed with laparoscopic appendicectomy once the diagnosis was confirmed. In cases of complicated appendicitis, the laparoscopic approach may be preferred over open approach [7].…”
Section: Appendicitismentioning
confidence: 99%
See 4 more Smart Citations
“…In 2012, grade A recommendation was made in EAES consensus statement [8] suggesting the use of diagnostic laparoscopy in suspected appendicitis and to proceed with laparoscopic appendicectomy once the diagnosis was confirmed. In cases of complicated appendicitis, the laparoscopic approach may be preferred over open approach [7].…”
Section: Appendicitismentioning
confidence: 99%
“…Hussain et al, in their prospective study, suggested that it may be a contributory factor in abdominal contamination [12]. However, it has been suggested that laparoscopy is better for lavage due to better visualization [13], and the EAES consensus statement of 2012 favours it [8].…”
Section: Appendicitismentioning
confidence: 99%
See 3 more Smart Citations